Advancements in DEMO WCLL breeding blanket design and integration. (11th May 2017) - Martelli, E.; Del Nevo, A.; Arena, P.; Bongiovì, G.; Caruso, G.; Di Maio, P. A.; Eboli, M.; Mariano, G.; Marinari, R.; Moro, F.; Mozzillo, R.; Giannetti, F.; et al.
Summary: The water‐cooled lithium–lead breeding blanket is a candidate option for the European Demonstration Power Plant (DEMO) nuclear fusion reactor. This breeding blanket concept relies on the liquid lithium–lead as breeder–multiplier, pressurized water as coolant, and EUROFER as structural material. The current design is based on DEMO 2015 specifications and represents the follow‐up of the design developed in 2015. The single‐module‐segment approach is employed. This is constituted by a basic geometry repeated along the poloidal direction. The power is removed by means of radial–toroidal (i.e., horizontal) water cooling tubes in the breeding zone. The lithium–lead flows in a radial–poloidal direction. On the back of the segment, a 100‐mm‐thick plate is in charge of withstanding the loads due to normal operation and selected postulated initiating events. Water and lithium–lead manifolds are designed and integrated with a consistent primary heat transport system, based on a reliable pressurized water reactor operating experience, and the lithium–lead system. Rationale and features of the single‐module‐segment water‐cooled lithium–lead breeding blanket design are discussed and supported by thermo‐mechanic, thermo‐hydraulic, and neutronic analyses. Preliminary integration with the primary heat transfer system, the energy storage system, and the balance of plant is briefly discussed. Open issues, areas of research, and development needs are finally pointed out. @EUROfusion Consortium*, 2017. *For more details see http://www.euro‐fusionscipub.org/disclaimer‐copyright Abstract : The paper concerns the new design of the water‐cooled lithium–lead breeding blanket, which is one of the candidate options for the European Demonstration Power Plant fusion reactor. The new design consists of a single‐module blanket segment concept and presents horizontal (i.e., radial–toroidal) water‐cooling tubes in the breeding zone, and lithium–lead flowing in the radial–poloidal direction. The paper presents the rationale and features of the water‐cooled lithium–lead breeding blanket design, supported by thermo‐mechanic, thermo‐hydraulic, magneto‐hydrodynamic, and neutronic analyses.